2004
DOI: 10.1590/s0034-72992004000300007
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da morfo e citodiferenciação da glândula submandibular remanescente de ratos após excisão parcial de um de seus lobos

Abstract: Manter uma boa saúde depende, entre outros fatores, de um fluxo salivar adequado1-3. Os danos causados por obstrução, traumas ou remoção cirúrgica das glândulas salivares poderão acarretar alteração na produção salivar. Qualquer diminuição no fluxo salivar trará conseqüências danosas ao organismo. Desenvolveu-se este trabalho com o objetivo de aprofundar o conhecimento nos mecanismos que envolvem a regeneração da Glândula Submandibular (GSM) de ratos submetida à excisão parcial de um de seus lobos. FORMA DE ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
0
0
1
Order By: Relevance
“…Histologically, our data showed that the characteristics of the acini and of the striated ductus of the collared peccary are similar to those reported in several animals, such as reported by Cowley et al, 6 Espinal et al, 19 and Nagato et al 20 On the other hand, the morphological characteristics of the ductal structures of the submandibular gland of the collared peccary may be different when compared with other mammals, such as the Koala (Phascolarctos cinereus). 3 Our data confirm that the nuclei were located in the basal region of the cells in spherical form, similar to those found in other mammals, such as reported by Estecondo et al 1 in the armadillo (Zaedyus pichiy) and by Fossati et al 21 in rats.…”
Section: Discussionsupporting
confidence: 91%
“…Histologically, our data showed that the characteristics of the acini and of the striated ductus of the collared peccary are similar to those reported in several animals, such as reported by Cowley et al, 6 Espinal et al, 19 and Nagato et al 20 On the other hand, the morphological characteristics of the ductal structures of the submandibular gland of the collared peccary may be different when compared with other mammals, such as the Koala (Phascolarctos cinereus). 3 Our data confirm that the nuclei were located in the basal region of the cells in spherical form, similar to those found in other mammals, such as reported by Estecondo et al 1 in the armadillo (Zaedyus pichiy) and by Fossati et al 21 in rats.…”
Section: Discussionsupporting
confidence: 91%
“…Este achado corrobora o estudo de Man et al, 15 ao constatar que as células dos ductos intercalares de glândulas submandibulares exibem relevante papel na renovação celular, tendo a possibilidade de sofrerem diferenciação em bloco para substituir os ácinos; além de contribuírem para a deposição adicional de células individuais nos limites entre os ductos intercalares com os ácinos e com os ductos estriados. Fossati et al, 16 acrescentam ainda que o desenvolvimento de todas as glândulas salivares é semelhante e que há um segmento ductal entre os ductos intercalares e estriados que secretam fatores de crescimento como fator de crescimento epidermal (EGF) e fator de crescimento de fibroblastos (FGF), entre outros, que influenciam na regeneração da glândula submandibular, e possivelmente nas demais glândulas salivares.…”
Section: Css Dss D-gln-s D-s-tre D-gln-treunclassified